EURAD state-of-the-art report: thermo-hydro-mechanical behaviour of clay buffers at high temperatures - Villar, María Victoria; Cernochova, Katerina; Cuevas, Jaime; Gens, Antonio; Gimeno, Natalia; Graham, Caroline; Harrington, Jon; Kašpar, Vlastislav; Kaufhold, Stephan; Leupin, Olivier; Mašín, David; Najser, Jan; et al. (Frontiers in Nuclear Engineering, 2025)
Most safety cases for radioactive waste disposal consider a temperature limit of 100°C for the clay buffers. Given that being able to tolerate higher temperatures would have significant advantages, the work package HITEC of the EURAD project aimed at determining the influence of temperature above 100°C on buffer properties, trying to establish if the safety functions are unacceptably impaired. A synthesis of the state of knowledge on the thermo-hydro-mechanical and chemical behaviours of different buffer materials at different temperatures is presented, along with the progress made in this area during HITEC. The changes in the properties of the preheated material and the hydromechanical properties of bentonite at high temperatures were assessed. To cover the first instance, bentonite was heated at 150°C in dry and wet conditions for different periods of time up to 2 years. The clay mineralogy was significantly preserved. The slight changes observed in the other properties were opposite depending on the heating conditions: in the case of evaporation, the cation exchange capacity, specific surface area, sorption coefficients, and sometimes swelling pressure decreased. These changes likely resulted from the strong drying induced by the elevated temperatures. Bentonite was also subjected to hydration under a thermal gradient in field and laboratory tests. No post-mortem structural modifications of the smectite were observed; however, dissolution and precipitation of species occurred, conditioned by the type of bentonite and hydration water. These processes were accompanied by the modification of the exchangeable cation complex. Determination of the hydromechanical properties of expansive clay at elevated temperatures is challenging owing to experimental and interpretation issues. In most cases, a reduced swelling pressure was obtained when the temperature increased, particularly at higher dry densities. These results may have been affected by the experimental protocols, use of bentonite or purified smectite, and exchangeable cations. Even at the highest temperatures, bentonite can fill voids and develop large swelling pressures at high densities. Thermo-hydro-mechanical models were developed or upgraded during the project to include thermal phenomena and dependencies and were applied to the simulation of new laboratory thermo-hydraulic tests in cells.